AGC703: Toxicology / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (2017)
Provide instruction, develop interest and promote further understanding of the organism, biochemical and molecular responses of insects to synthetic and biological insecticides and plant compounds. Guide students to achieve an integrative perspective of the process of chemical poisoning of insects in relationship to, and on the bases of their previously acquired knowledge in insect physiology. Explain the molecular basis of insecticide selectivity, efficacy and safety, and the mechanisms and molecular genetics of insecticide resistance. Introduce students to the applications of molecular biology to insect toxicology. Explain the molecular basis of insecticide selectivity, efficacy and safety, and the mechanisms and molecular genetics of insecticide resistance. Introduce students to the applications of molecular biology to insect toxicology. Discuss transgenic technology available for pest control. Introduce students to the applications of molecular biology to insect toxicology. Discuss transgenic technology available for pest control.